Simulation Survey of RSA and Its Variants - Kumar, R; Jain, AK (International Journal of Computer Sciences and Engineering, 2025)
Cryptography is used in securing data transmission over insecure networks. The selection of algorithm requires the condition of fulfillment of authentication, confidentiality, integrity and non-repudiation. Among all public key encryption algorithms, RSA is globally accepted encryption algorithm due to its hardness against various possible attacks. In this paper, we studied RSA, enhanced RSA, Elgamal, chinese remainder theorem (CRT) based RSA, multi-power RSA, three-prime RSA and Elgamal-RSA cryptosystem.